An Investigation of Growth Time of Homoepitaxial Synthesis of ZnO Nanorods via Hydrothermal Method. Issue 7 (2nd July 2016) - Ghayour, Hamid; Nekoubin, Amin; Nourbakhsh, Amir Abbas
Abstract : In this research, ZnO nanorods were prepared via hydrothermal method on the seed layer. The seed layer was prepared through the sol-gel high-speed spin coating process. The effect of concentration of precursors and growth time on the size and alignment ordering of these hexagonally structured nanorods was studied by scanning electron microscopy, high-resolution transmission electron microscopy, and X-ray diffraction. Results showed that under the conditions of hydrothermal growth and in the presence of seed layer, the concentration of precursors influences diameter, length, and density of nanorods. Concentration also improves the alignment ordering of the nanorods, so that compared with lower concentrations, despite the increase of rod diameter by increase of concentration, the alignment ordering of the rods significantly improves. Also, the growth time has significant effect on the length, diameter, and aspect ratio of ZnO nanorods.